Sustainable solid waste management system using multi-objective decision-making model: a method for maximizing social acceptance in Hoi An city, Vietnam - Hoang, Giang Minh; Fujiwara, Takeshi; Pham Phu, Toan Song; Nguyen, Luong Duc (Environmental science and pollution research international, 2019)
The main aim of this study was to develop a decision support system for sustainable municipal solid waste management (MSWM) in Hoi An city (HAC), Vietnam. A face-to-face interview was conducted with local experts including authorities, citizens, waste collection contractors and recyclers to identify main objectives of waste management system and appropriate treatment methods. A multi-objective optimization model was proposed using non-linear programming approach. An interactive method known as reference point method (RPM) was applied for solving the problem with three objectives including cost minimization, landfill minimization and emission minimization. As a result, the efficient waste-flow-allocation and the optimal capacity of disposal facilities were determined by intense discussion and agreement among decision-makers. Waste incineration, anaerobic digestion, sanitary landfill and current recycling activities should be applied with a cost of about 2300 US$ daily. Also, the daily emission of various pollutants was about 35 metric tons, and the greenhouse gas (GHG) is 313 tons CO 2-eq .